Is the Use of Glyphosate in Modern Agriculture Resulting in Increased Neuropsychiatric Conditions Through Modulation of the Gut-brain-microbiome Axis? - Barnett, Jacqueline A.; Bandy, Maya L.; Gibson, Deanna L. (Frontiers in Nutrition, 2022)
Environmental exposure to glyphosate and glyphosate-based herbicides has the potential to negatively influence neurodevelopment and behaviour across generations indirectly through the gut-brain axis. Potential mechanisms by which glyphosate may elicit these effects are through the disruption of the normally symbiotic relationship of the host and the gut microbiome. Given glyphosate can kill commensal members of the microbiome like Lactobacillus spp., Ruminococaeae and Butyricoccus spp., this results in reductions of key microbial metabolites that act through the gut-brain axis including indoles, L-glutamate and SCFAs. Glyphosate-resistant microbes in the gut have the potential to increase the production of pro-inflammatory cytokines and reactive oxygen species in which may result in increased HPA activation, resulting in increased production of glucocorticoids which have implications on neurodevelopment. In addition, maternal transfer of the gut microbiome can affect immune and neurodevelopment, across generations. This perspective article weighs the evidence for chronic glyphosate exposure on the gut microbiome and the potential consequences on the gut-brain axis correlated with increased incidence of neuropsychiatric conditions.